2008
DOI: 10.1080/15287390801906675
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Biological Activity Between Ultrafine and Fine Titanium Dioxide Particles in RAW 264.7 Cells Associated with Oxidative Stress

Abstract: Ultrafine or fine titanium dioxide (TiO(2)) particles are widely used in the production of white pigments, for sunscreens, and in cleanup techniques. However, currently knowledge is deficient concerning cellular responses to these particles. The study evaluated and compared the biological activity of ultrafine and fine TiO(2) particles in RAW 264.7 macrophages according to an oxidative stress paradigm. In vitro exposure of macrophages to ultrafine or fine TiO(2) in the range of 0.5-200 microg/ml did not signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 33 publications
3
44
1
Order By: Relevance
“…Bioluminescent bioreporters have been used to study the toxicity effects of carbon-based nanomaterials (Jia et al 2014a;Kang et al 2008;Lee et al 2014), but few studies centered specifically on the toxicity of CNCs have been reported. In this work, our aim is to apply the bioluminescent bioreporter E. coli 652T7 for profiling the biological toxicity of CNCs to establish a more comprehensive risk assessment knowledge base.…”
Section: Introductionmentioning
confidence: 99%
“…Bioluminescent bioreporters have been used to study the toxicity effects of carbon-based nanomaterials (Jia et al 2014a;Kang et al 2008;Lee et al 2014), but few studies centered specifically on the toxicity of CNCs have been reported. In this work, our aim is to apply the bioluminescent bioreporter E. coli 652T7 for profiling the biological toxicity of CNCs to establish a more comprehensive risk assessment knowledge base.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies proposed oxidative stress as a key mechanism involved in the toxicity of various nanomaterials [31,[45][46][47] that results from the imbalance between excessive [12,31,40,48], which is based on the conversion of the non-fluorescent 2 0 ,7 0 -dichlorodihydrofluorescein diacetate to the highly fluorescent 2 0 ,7 0 -dichlorofluorescein; the substrate is oxidized preferentially by peroxides [39,49]. GO enhanced the formation of intracellular ROS in both A549 and RAW 264.7 cells at the highest concentration of 12.5 lg/cm 2 up to 3.5-times compared to control cells, already after 30 min (Fig.…”
Section: Generation Of Reactive Oxygen Species (Ros) By Graphene Oxidementioning
confidence: 99%
“…The original method was described by Wan et al [39], and has been already used in other studies on NM toxicity [12,31,40] and moreover, it is the assay recommended by the NANOMMUNE consortium http://ki.projectcoordinator.net/projectweb/490599f501abc/ Index.html). The non-fluorescent 2 0 ,7 0 -dichlorodihydrofluorescein diacetate (H 2 DCF-DA, Molecular Probes) is a cell permeable dye due to its diacetate group.…”
Section: Reactive Oxygen Species (Ros) Detectionmentioning
confidence: 99%
“…Rats exposed to three forms of ultrafi ne TiO 2 particles and quartz particles confi rmed that the quartz produced greater pulmonary infl ammation, cytotoxicity, and adverse lung tissue effects than rutile and anatase/ rutile UFPs, suggesting that crystal structure, inherent pH of the particles, and surface chemical reactivity are important determinants of UFP toxicity (Warheit et al, 2007 ). Comparison of the oxidative potential between ultrafi ne and fi ne TiO 2 in vitro found that, at equivalent mass, TiO 2 NPs were more potent in inducing intracellular generation of reactive oxygen species, extracellular regulated kinase (ERK) phosphorylation, and release of tumor necrosis factor -alpha (TNF -α ) and MIP -2 than fi ne TiO 2 (Kang et al, 2008 ). In monocytic cells, ultrafi ne TiO 2 induced MAP kinase activation and release of infl ammatory mediators in a concentration -dependent manner.…”
Section: Metal -Based Np S and Cardiovascular Effectsmentioning
confidence: 99%